RETRACTED: Abscisic Acid Is Required for Root Elongation Associated With Ca2+ Influx in Response to Water Stress - Yuan, Wei; Zhang, Qian; Li, Ying; Wang, Qianwen; Xu, Feiyun; Dang, Xiaolin; Xu, Weifeng; Zhang, Jianhua; Miao, Rui (Frontiers in Plant Science, 2020)
Abscisic acid (ABA) is a critical hormone for plant survival upon water stress. In this study, a large-scale mutants of Arabidopsis ecotype Columbia-0 (Col-0) by ethyl methanesulfonate (EMS)-mutagenesis were generated, and an improved root elongation under water-stress 1 (irew1) mutant showing significantly enhanced root growth was isolated upon a water potential gradient assay. Then, irew1 and ABA-related mutants in Arabidopsis or tomato plants were observed under water potential gradient assay or water-deficient condition. ABA pathway, Ca2+ response and primary root (PR) elongation rate were monitored in addition to DNA- and RNA-Seq analyses. We found that based on phenotyping and transcriptional analyses, irew1 exhibited the enhanced PR growth, ABA and Ca2+ responses compared to wild-type subjected to water stress. Interestingly, exogenous Ca2+ application enhanced PR growth of irew1, ABA-biosynthesis deficient mutants in Arabidopsis and tomato plants in response to water potential gradients or water-deficient condition. In combination with other ABA-related mutants and pharmacological study, our results suggest that ABA is required for root elongation associated with Ca2+ influx in response to water stress.